A supervisão educacional de Moçambique: entre o centralismo burocrático e a descentralização democrática - Selimane, Remane (2015)
Educational Supervision (E.S.) is the subject of this research. It assesses the possibilities of reducing bureaucracy, decentralization and democratization of this process in the context of the Education in Mozambique. The aim is to contribute to the promotion of strategies for concerted, coordinated, mutually influential and useful actions and their suitability to the current stage of the Education in Mozambique. Based on self-reflection on the search for a social identity of the supervisory function and action, we cast a look to the efforts of its replacement in the place that it deserves. Relying on critical theory and in formulations that articulate an ontology based on historical realism, in a transactional epistemology, both dialectic and dialogic, we search for a qualitative aspect, through bibliographic and documentary research; critical discourse analysis, which intersects with the approach of the Policy Cycle, observation and questionnaires, intermingled with the history of professional life. The dynamics of this research provides, in methodological discussions, through the theoretical framework, to literature review about the Educational Supervision, centralization versus decentralization, including reflections on the national systems of education, an interesting dialogue among several authors such as Enrique Dussel (2012), Dermeval Saviani (2014, 2010), Gimeno Sacristán & Pérez Gómez (1998), Michel Foucault (2014, 2011), Richard Bowe and Stephen Ball (1992), Formosinho et al (1999), Uwe Flick (2009), Norman Denzin & Yvonna Lincoln (2006); Alarcão (2014, 2013, 2001, 2000, 1996); Alonso (2010); Ferreira (2013a, 2013b, 2010,2002); Rangel (2013a, 2013b, 2011, 2010, 2008); Silva Júnior (2011a, 2011b, 2010). The research recovers the historical traditions of the E.S. in the country, its vertical joints, searching to peer at the developments of the hierarchical structure of the system and the horizontal, those that occur within the governing bodies, seeking to understand the joints amongst the sub-sectors of the subsystems, as well as between administrative aspects and also pedagogical aspects; it establishes the relationship between the adopted curriculum options and modalities and forms of developed Educational Systems, and also its relationship with the school pedagogical practices as well as the roles and responsibilities of the person in charge of the process and the relations with each other; together with documentary research and the content of what we are given by voice and turn of the persons in charge, in between with the revised theory, it outlines a practical layout of a desired Mozambican educational supervisor and extract the subjective theory it crystallized. The theoretical framework is in the key subject seeking to understand the supervisory action since its inception, its changes of the function, given its constant, permanent and continuous redefinition. In short, it render problematic the National Education System, that in fact does not seem to actually exist as such and, in addition to finding of a close relationship but dependence between a misconception of the curriculum, there are signs of disputes of the desirable supervisory function, which epicenter seems to lie precisely at the Ministry of Education, thus, this situation tends to keep the body of local management of education in a subordinate position, and consequently, their dependence on central bodies tend to be perpetuated. Besides, the research makes visible possibilities to face changes with regard to the place status and ways in which the activity is being developed in Mozambique